Threats and Opportunities of Using IoT in Cyberspace as a New Combat Environment - Maciej MARCZYK; Grzegorz PILARSKI (Communications of International Proceedings, 2021)
The article presents the chances and threats inherent in the use of the Internet of Things (IoT) as a modern technology in cyberspace, which is understood as a dynamically changing combat environment. The authors attempt to find answers to the following question: What is the scope and the effect of using IoT in cyberspace as a new warfare environment? Presently, cyberspace provides chances and possibilities to apply groundbreaking technologies, such as IoT, which might have a direct effect on the state’s defence and the armed forces. The research problem concerns the assessment of the utility and usefulness of IoT in the military sphere. The analysis of the available factual sources allowed to identify a new warfare environment, namely cyberspace and the possibilities of IoT application by the armed forces. The military application of IoT provides potential possibilities. Nonetheless, too weak protection against cyber attacks might limit the use of the long-range technology in the sphere that is not directly related to warfare operations.
Keywords: cyberspace; new technologies; Internet of Things (IoT)